2021
DOI: 10.1038/s41598-021-90645-1
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome resequencing of large yellow croaker (Larimichthys crocea) reveals the population structure and signatures of environmental adaptation

Abstract: Large yellow croaker is an economically important fish in China and East Asia. Despite its economic importance, genome-wide adaptions of domesticated large yellow croaker are largely unknown. Here, we performed whole-genome resequencing of 198 individuals of large yellow croaker obtained in the sea or from farmers in Zhoushan or Ningde. Population genomics analyses revealed the genetic population structure of our samples, reflecting the living environment. Each effective population size is estimated to be decl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…So far, it has been extensively applied in a large number of plants and animals, such as maize ( Zea mays ssp. mays L.) (Wang et al, 2020 ), rice ( Oryza sativa L.) (Yano et al, 2016 ), chicken ( Gallus gallus ) (Rubin et al, 2010 ), sheep ( Ovis aries ) (Li et al, 2020 ), Atlantic salmon ( Salmo salar ) (Bertolotti et al, 2020 ), large yellow croaker ( Larimichthys crocea ) (Kon et al, 2021 ), and black tiger shrimp ( Penaeus monodon ) (Wong et al, 2020 ). In the present study, in order to profile genome signatures of selection in Pacific oyster, we performed whole‐genome resequencing of 20 oysters from two fast‐growing strains and 20 oysters from their corresponding wild populations.…”
Section: Introductionmentioning
confidence: 99%
“…So far, it has been extensively applied in a large number of plants and animals, such as maize ( Zea mays ssp. mays L.) (Wang et al, 2020 ), rice ( Oryza sativa L.) (Yano et al, 2016 ), chicken ( Gallus gallus ) (Rubin et al, 2010 ), sheep ( Ovis aries ) (Li et al, 2020 ), Atlantic salmon ( Salmo salar ) (Bertolotti et al, 2020 ), large yellow croaker ( Larimichthys crocea ) (Kon et al, 2021 ), and black tiger shrimp ( Penaeus monodon ) (Wong et al, 2020 ). In the present study, in order to profile genome signatures of selection in Pacific oyster, we performed whole‐genome resequencing of 20 oysters from two fast‐growing strains and 20 oysters from their corresponding wild populations.…”
Section: Introductionmentioning
confidence: 99%
“…As geographical stock delimitation based on morphology is often inconsistent with analysis results based on molecular data, determining the accurate genetic structure is of particular concern. A series of studies based on molecular markers have been conducted since the last decade in wild and cultured populations of large yellow croaker, but these studies were limited in terms of their success in determining population structure and phylogeography due, for instance, to sampling only part of the distribution area (Wang et al, 2012(Wang et al, , 2014Kon et al, 2021), small sample size in one group (Wang et al, 2013;Han et al, 2015); or collecting cultured populations from only a few farms (Huang et al, 2012;Wang et al, 2012;Kon et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified selection signatures in several aquaculture fish species, including large yellow croaker ( Kon et al, 2021 ), Amur ide ( Wang et al, 2021a ), Atlantic salmon ( Gutierrez et al, 2016 ; López et al, 2019 ), Nile tilapia ( Cádiz et al, 2020 ; Nayfa et al, 2020 ), and brown trout ( Lemopoulos et al, 2018 ). To date, however, genomic selection signatures of the largemouth bass have not been reported.…”
Section: Discussionmentioning
confidence: 99%